HAX-1 Protects Glioblastoma Cells from Apoptosis through the Akt1 Pathway - Deng, Xin; Song, Laijun; Zhao, Wen; Wei, Ying; Guo, Xin-bin (Frontiers in Cellular Neuroscience, 2017)
Hematopoietic-substrate-1 associated protein X-1 (HAX-1) has been reported as an anti-apoptosis protein that plays an important role in several malignant tumors. However, the effect and mechanism of HAX-1 in glioblastomas remains unknown. This study investigated the effect of HAX-1 in glioblastoma cells and explore the mechanism. The results of clone formation and Edu proliferation assay showed slower multiplication in HAX-1 knock-out cells. Apoptosis due to oxidative stress was increased after HAX-1 was knocked out. Western-blot assay exhibited that the levels of p21, Bax, and p53 proteins were significantly raised, and that the activation of the caspase cascade was enhanced in the absence of HAX-1. The degradation rate and ubiquitination of p53 declined because of the decrease in phosphorylation of proteins MDM2 and Akt1. Co-immunoprecipitation (Co-IP) and immunefluorescent co-localization assays were performed to test the influence of HAX-1 on the interaction between Akt1 and Hsp90, which is crucial for the activity of Akt1. In conclusion, this study suggested that HAX-1 could affect the Akt1 pathway through Hsp90. The knock-out of HAX-1 leads to the inactivity of the Ak1t/MDM2 axis, which leads to increased levels of p53, and finally generates cell cycle arrest and results in the apoptosis of glioblastoma cells.